The Disutility of Injustice - Goodwin, Geoffrey P (2010)
For more than half a century, the retributivists and the crime-control instrumentalists have seen themselves as being in an irresolvable conflict. Social science increasingly suggests, however, that this need not be so. Doing justice may be the most effective means of controlling crime. Perhaps partially in recognition of these developments, the American Law Institute's recent amendment to the Model Penal Code's purposes provision – the only amendment to the Model Code in the 47 years since its promulgation – adopts desert as the primary distributive principle for criminal liability and punishment. That shift to desert has prompted concerns by two groups – ironically, two groups traditionally opposed to one another. The first group – those concerned with what they see as the over-punitiveness of current criminal law – worries that setting desert as the dominant distributive principle means continuing the punitive doctrines they find so objectionable, and perhaps will make things worse. The second group – those concerned with ensuring effective crime control – worries that a shift to desert will create many missed crime-control opportunities; it will increase avoidable crime. The first group's concern about over-punitiveness rests upon an assumption that the current punitive crime-control doctrines of which they disapprove are a reflection of the community's naturally punitive intuitions of justice. However, as Study 1 makes clear, today's popular crime-control doctrines in fact seriously conflict with people's intuitions of justice by exaggerating the punishment deserved. The second group's concern that a desert principle will increase avoidable crime exemplifies the common wisdom of the past half century that ignoring justice in pursuit of crime-control through deterrence, incapacitation of the dangerous, and other such coercive crime-control programs is cost free. However, Studies 2 and 3 suggest that doing injustice has real crime control costs. Deviating from the community's shared principles of justice undermines the system's moral credibility and thereby undermines its ability to gain cooperation and compliance and to harness the powerful forces of social influence and internalized norms. The studies reported here give assurance to both groups. A shift to desert is not likely to either undermine the criminal justice system's crime-control effectiveness, and indeed it may enhance it, nor is it likely to increase the system's punitiveness, and indeed it may reduce it